Pengaruh Metode Listen for Lies Games Terhadap Pemahaman Mufradat Siswa - Siti Jurotul Wahyu; Syaifullah (CV. Satria Jaya, 2024)
Problems in schools about understanding vocabulary, especially Arabic vocabulary, have until now become a problem in Islamic-based schools. Because students feel objections and difficulties in learning vocabulary in learning Arabic. The purpose of this study is to increase students' understanding of vocabulary through the listen for lies games method. This study uses quantitative research methods with experimental types. The experimental design used is a pre-experimental design with the type of one group pretest posttest. To collect data, the methods used are test, observation, and documentation. Hypothesis testing and research analysis using normality test, T-test, and F test (Anova). Based on the T-test, the average value of the pretest of students is 54.6667 with a minimum score of 20 and a maximum of 100. While the posttest average value is 90.333 with a minimum score of 70 and a maximum value of 100. This shows that there is an escalation in students' understanding of vocabulary. using the listen for lies games method. Based on the F test, the value of sig 0.018 <0.05, then the effect of the listen for lies games method on students' understanding of vocabulary.